JAVANESE ENDEMIC STROBILANTHES(ACANTHACEAE): TAXONOMY, DISTRIBUTION AND CONSERVATION STATUS - Yasper Michael Mambrasar; Yayah Robiah; Nira Ariasari Z.; Yayan Supriyanti; Dewi Rosalina; Sutikno Sutikno; Jaenudin Jaenudin; Wahyudi Santoso; Dede Surya; Megawati Megawati; Taufik Mahendra; Agusdin Dharma Fefirenta; Deby Arifiani (BERITA BIOLOGI, 2020)
The taxonomic status of Javanese Strobilanthes has been revised by Bennett and Scotland (2003). However, the results of the validation of the Javanese Acanthaceae by Girmansyah (2014) show that several Strobilanthes species, especially those endemic to Java, need to be revised. Because they have become synonymous. Conservation status of Javanese endemic Strobilanthes was carried out according to the IUCN Red list Categories and Criteria.